Medan The Vertical Village Design In Kelurahan Aur (With Ecology Architecture Design Approach) - Ivany Hidayat; Wahyuni Zahrah (Talenta Publisher, 2017)
Kampung Aur is one of the densely populated settlements located in Medan City Center. This village is located on the banks of the River Deli, District Mimoon Medan, Neighborhood IV. Kampung Aur is a place for the lower middle-class urban community that provides a place for unplanned settlements. This village has the potential to be reorganized while maintaining the traditions of the people. The approach used for the design of this village is Ecological architecture, where the building uses a natural building system, wastewater treatment, and rainwater utilization.